Revisiting how knowledge economy of the centre sustains rural poverty and underdevelopment in Africa - Matunhu, Jephias (Midlands State University, 2016)
Rural areas in Africa carry over 60 percent of the population in the continent. Yet they are the poorest parts of the world. Since a while now, the United Nations, governments, non-governmental organizations and individuals have been grappling with the problem of rural underdevelopment in Africa. Conventions have been signed; strategic plans have been adopted and set in motion and donations have been channeled to Africa to alleviate the plight of rural communities. Despite all the effort, rural poverty and underdevelopment continue to disfigure the continent, albeit some improvement. Why is it taking so long to heave the rural communities out of poverty and underdevelopment? The theoretical discourse claims that the problem lies in the differences in the knowledge economies of the affluent communities (the centre) and the poor and sometimes desperate rural communities (periphery). The discourse concludes that merging the traditional knowledge economies of Africa and that of the West is what would sustain rural development in the continent.